UPAYA MENINGKATKAN PERTUMBUHAN TERNAK KELINCI DI DASAN KARANG ANYAR DESA SIKUR LOMBOK TIMUR - Sumiati, Sumiati; Wiryawan, I Ketut Gede; Erwan, Erwan; Purnamasari, Dwi Kusuma; Maslami, Vebera; Syamsuhaidi, Syamsuhaidi (Universitas Mataram, 2024)
Service to the community in the village of Karang Anyar Sikur Village, East Lombok, aims to improve knowledge breeders skill especially breeders rabbit that is in through making and giving quality feed. The population and growth of rabbits in Karang Anyar Sikur Village, East Lombok is relatively low compared to other villages in East Lombok, this is due to the lack of knowledge about the management of feeding rabbits, including the quality and quantity of feed provided. The implementation of the activity is carried out gradually, starting from the survey location, setting the time for implementation, making the brochure/leaf, and watching the video about the cultivation of the rabbit and the evaluation stage. By achieving the goal of this activity, it is expected that the community, especially the pet group, will be able to make formulas for the rabbit's food from the materials that are available at the location, with the content of the nutrition, according to the needs of the rabbit, and the provision of good food, so that it can increase the growth of the rabbit Income breeders rabbit.